TRANSFORMATION OF REGULATORY COMPLIANCE IN THE PUBLIC SECTOR WITH ARTIFICIAL INTELLIGENCE (International Seven Journal of Multidisciplinary, 2024)
The implementation of Artificial Intelligence (AI) in the context of regulatory compliance in the public sector has the potential to revolutionize administrative processes, improving the accuracy and efficiency of public institutions. AI's ability to analyze large volumes of data in real-time enables more effective identification of regulatory violations, contributing to a more transparent and efficient system. Additionally, AI can optimize the detection of irregularities, such as fraud and resource misallocation, strengthening public governance. However, the adoption of this technology requires a robust data infrastructure, as well as continuous training for public servants to ensure the proper use of these tools. It is essential that AI implementation is accompanied by appropriate governance frameworks to ensure accountability and ethics in automated processes. Clear and transparent regulations are crucial to mitigate risks related to automation, ensuring that AI-driven decisions are understandable and auditable. Collaboration between technology developers, regulators, and decision-makers is key to ensuring that AI is used responsibly and effectively. With this, AI has the potential to reduce costs, increase operational efficiency, and promote public administration more aligned with contemporary regulatory needs and requirements.